Chronic Administration of Melatonin: Physiological and Clinical Considerations - Donald Givler; Amy Givler; Patrick M. Luther; Danielle M. Wenger; Shahab Ahmadzadeh; Sahar Shekoohi; Amber N. Edinoff; Bradley K. Dorius; Carlo Jean Baptiste; Elyse M. Cornett; Adam M. Kaye; Alan D. Kaye (Neurology International, 2023)
Background: Exogenous melatonin is commonly used to treat insomnia, other sleep problems, and numerous medical illnesses, including Alzheimer’s disease, autism spectrum disorder, and mild cognitive impairment in adults and children. There is evolving information regarding issues with the use of chronic melatonin. Methods: The present investigation was a narrative review. Results: Melatonin usage has risen dramatically in recent years. Many countries only allow melatonin prescriptions. In the United States (U.S.), it is classified as a dietary supplement accessible over the counter and can be derived from animals, microorganisms, or, most commonly, made synthetically. No regulatory agency oversees its manufacturing or sale in the U.S. melatonin concentration of marketed preparations varies widely between product labels and manufacturers. Melatonin’s ability to induce sleep is detectable. However, it is modest for most people. Sleep length appears to be less important in sustained-release preparations. The optimal dosage is unknown, and routinely used amounts vary substantially. Melatonin’s short-term negative effects are minimal, resolve at medicine cessation, and do not usually prevent usage overall. Much research on long-term melatonin administration has found no difference between exogenous melatonin and placebo in terms of long-term negative effects. Conclusion: Melatonin at low to moderate dosages (approximately 5–6 mg daily or less) appears safe. Long-term usage appears to benefit certain patient populations, such as those with autism spectrum disorder. Studies investigating potential benefits in reducing cognitive decline and increased longevity are ongoing. However, it is widely agreed that the long-term effects of taking exogenous melatonin have been insufficiently studied and warrant additional investigation.